Ways to Improve the Efficient Operation of Digital Banks in Uzbekistan - M. Vakhabova; Scientific Supervisor: R. Sh. Salaev (European Science Publishing, 2024)
The article focuses on digital banking, which is a new and fast-growing trend in banking. The article analyzes the ways of development of digital banking and transformation of banks, examines models of digital banking in developed countries and possible ways of their application in Uzbekistan.
Keywords: digitalization, financial technology, digital bank, remote banking, mobile banking.